Wear mechanism of flexspline materials regulated by novel amorphous/crystalline oxide form evolution at frictional interface. (July 2019) - Zhang, Caixia; Song, Zhiqiong; Liu, Zhifeng; Cheng, Qiang; Zhao, Yongsheng; Yang, Congbin; Liu, Mengmeng
Abstract: Flexspline is the most vulnerable component of harmonic drives, and its wear is likely to induce failure. Therefore, this study investigated the tribological properties of three typical flexspline materials with lubricating grease. The evolution of two oxide forms (amorphous FeOOH and crystalline Fe2 O3 ) on a frictional interface was proposed as the wear mechanism, and this mechanism was confirmed using co-analyses of X-ray photoelectron spectroscopy, transmission electron microscopy, atomic force microscopy, and scanning electron microscopy. Amorphous FeOOH generated during sliding was observed to enhance the oxide layer, resulting in compact structure and improved toughness that reduced friction at the interface, whereas with insufficient amorphous FeOOH, the frictional crystalline Fe2 O3 tended to strip under shear force, destabilizing the oxide layer. The formation ratio of FeOOH/Fe2 O3 during sliding regulated the oxide film characteristics and the tribological properties of the materials. Crystalline Fe2 O3 partly evolved from amorphous FeOOH is mainly dependent on heat generated during sliding. The grease adsorption properties of tribo-pairs significantly affected the temperature of the frictional contact interfaces. The characteristics of this wear mechanism can be leveraged to reduce wear in future drive designs. Graphical abstract: Image 1 Highlights: A wear mechanism for flexspline materials is proposed, whereby the wear is regulated by two oxide forms evolving. The amorphous FeOOH generated during sliding gives the oxide layer a more compact structure, reducing friction. The frictional crystalline Fe2 O3 partly evolves from the amorphous FeOOH, triggering severe wear. The formation ratio of FeOOH/Fe2 O3 during sliding regulates oxide film characteristics and tribological properties.